PENGARUH TRADISI LOKAL TERHADAP WAJAH KEISLAMAN MASYARAKAT INDONESIA - Alam Sriyanto (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Before the arrival of Islam Indonesian tribes have lived regularly with animism religion as its spiritual roots and costumary laws as their social institutions, even sturdy rooted in Indonesian society has the ability elastic so it can survive eventhough have to deal with an excellent culture of teheir culture. The tradition that was born from the original Indonesian tribes is strong, forcing foreign cultures who seek to enter into these people's lives to be more linient and even had to adjust to the local people's traditions. Tolerant attitude towards the old culture done by preachers in spreading Islam in the archipelago in the early was quite successful. The consequence has been to make the face and character of Indonesian Islam different from Islam character of the face or anywhere in the world that even though Islam is the religion of the majority of the Indonesian population, but Islamic ritual pratices that they are doing much influenced by local traditions.